Answer:
[tex]y=9e^{-7x}cos(6x)+\frac{71}{6}e^{-7x}sin(6x)[/tex]
Step-by-step explanation:
The Given diffrential equation can be written as follows
[tex](D^{2}+14D+85)y=0[/tex]
Solving the auxiliary equation we get
[tex]D^{2}+14D+85=0[/tex]
Comparing with the standard quadratic equation [tex]ax^{2}+bx+c=0[/tex] we get
[tex]D=\frac{-b\pm \sqrt{b^{2}-4ac}}{2a}[/tex]
Using the values we get the roots as [tex]-7\pm 6i[/tex]
The roots are imaginary and conjugate
For a auxillary equation with roots [tex]a\pm bi[/tex] the solution is given by
[tex]y=c_{1}e^{ax}cos(bx)+c_{2}e^{ax}sin(bx)[/tex]
Applying values we get the solution of the equation as
[tex]y=c_{1}e^{-7x}cos(6x)+c_{2}e^{-7x}sin(6x)[/tex]....................(i)
here [tex]c_{1},c_{2)[/tex] are constants whose values shall be obtained using the given boundary conditions y(0) = 9 ; y'(0) = 8
In equation i putting x = 0 we get
9 =[tex]c_{1}[/tex]
Now we have
[tex]y'=-7c_{1}e^{-7x}cos(6x)-6c_{1}e^{-7x}sin(6x)-7c_{2}e^{-7x}sin(6x)+6c_{2}e^{-7x}cos(6x)[/tex]
Now y'(0) = 8
Thus we get
[tex]8=-7c_{1}+6c_{2}[/tex]
Solving for [tex]c_{2}[/tex] we get
[tex]c_{2}=71/6[/tex]
Thus the solution becomes
[tex]y=9e^{-7x}cos(6x)+\frac{71}{6}e^{-7x}sin(6x)[/tex]